Mengenalkan Mitigasi Bencana dalam Praktik Kerja Lapangan di Lingkungan Kelurahan. - Harrys Cristian Vieri; Hairani Siregar (JOURNAL SAINS STUDENT RESEARCH, 2023)
Field work practice or what is usually referred to as practicum is an activity held to practice the material that has been provided during teaching and learning activities. Fieldwork practice itself emerged with the existence of "Applied Science" knowledge, namely knowledge that is applied in nature, meaning it can be used directly in daily activities. History records that Field Work Practices appeared in Indonesia when they were first introduced in the Dual System Education (PSG) curriculum which is also known as Industrial Work Practices (PRAKERIN). Since 1994, Vocational High Schools throughout Indonesia have carried out this activity, followed by study programs at college level throughout Indonesia. Field Work Practices have several objectives, including producing professional workers appropriate to the work field, introducing practitioners to actual conditions in the field, and developing collaboration between educational institutions and the world of work to align education and training of quality workers. This is also what is done by the Social Welfare study program, Faculty of Social and Political Sciences, University of North Sumatra. As an "Applied Science" study program, USU Social Welfare holds Field Work Practices to prepare its students as experts in the field of social work.